Optimal and robust scheduling for networked control systems - Longo, Stefano. (Automation and control engineering., 2013)
"This book offers a tool for optimal/robust control system integration via communication networks. This work is shaped around examples and relevant standards of the automotive industry for those examples but the concepts are readily extendable to any application that uses deterministic communication protocols between system components (avionic systems, robots, etc.). The underlying idea is to use the rigorous tools from optimal and robust multivariable control theory to solve the industrial scheduling problem in a transparent manner"--